Trajectories of alcohol use and binge drinking among pregnant Inuit women - Fortin, Marilyn; Anassour-Laouan-Sidi, Elhadji; Bélanger, Richard E.; Muckle, Gina; Jacobson, Sandra W.; Jacobson, Joseph L. (Alcohol and Alcoholism, 2016)
Background: This study investigated trajectories of alcohol use and binge drinking among Inuit women starting from a year before pregnancy until a year after delivery, examined transition rates between time periods, and established whether specific factors could be identified as predictors of changes in alcohol behaviors. Methods: Drinking trajectories and movement among alcohol users and binge drinkers (i.e., non-binging and binging) were explored by Markov modeling across time periods. Two hundred and forty-eight Inuit women from Arctic Quebec were interviewed at midpregnancy, and at 1 and 11 months postpartum to obtain descriptive data on alcohol use during the year before pregnancy, the conception period, the pregnancy and the year after delivery. Results: The proportions of drinkers and bingers were 73% and 54% during the year prior to pregnancy and 62% and 33% after delivery. Both alcohol use and binge drinking trajectories demonstrated a significant drop in prevalence between the year before conception to the conception period. We also noted high probabilities of becoming an abstainer or not binging at this time. However, up to 60% of women continued to drink alcohol during pregnancy. Women in couples and not consuming marijuana were more likely to decrease their binge drinking at conception. Conclusions: This study emphasizes the importance of including the period around conception in the definition of drinking patterns during pregnancy. The importance of considering alcohol consumption in a multidimensional way (personal, familial and social determinants) is also addressed while trying to minimize problems both for the fetus and the mother.